Detecting Sodium Borax in Meat Processed Food Using Turmeric - Sri Wahyu Tarigan; Delima Sitanggang (Jurnal Mantik, 2020)
Borax as a dangerous preservative has been informed by the government by prohibiting the use of borax to preserve food. The use of borax is specifically regulated and limited by national health and safety laws. In simple terms, borax can be recognized by its presence in food by using a toothpick covered with turmeric. Toothpicks that have been smeared with turmeric will turn yellow according to the color of the turmeric but will turn orange when they are pricked into processed meat foods such as meatballs, sausages, and nuggets that contain borax. This is because turmeric contains curcumin which can detect the presence of borax in food. After all, curcumin can break down the borax bonds into boric acid and bind it to a complex rosin compound or commonly known as a boron cyano curcumin complex. The results of testing samples taken from two supermarkets and three traditional markets using turmeric as a reagent and the medium were toothpicks showed that 74% of processed food, including meatballs, nuggets, and sausages, contained borax and 26% did not contain borax